TUGAS GURU SEBAGAI PENGEMBANG KURIKULUM - Azhar M. Nur (Jurnal Ilmiah Didaktika, 2011)
Teacher as a curriculum developer has to be able to translate, explain and transform the values involved in the curriculum to his/her students. To develop the curriculum, a teacher can do the following activities, they are: planning, implementing and evaluating the curriculum. Through planning the curriculum, the teacher can predict what he/she want to achieve in the learning process. After planning, he/she should implement it. There are some steps the teacher can do in teaching such as preparing his/her students, explaining the material, assessing students and getting feedback to know the successful of teaching.